Chemical composition, in vitro rumen profile and methane emission of fermented and non-fermented grass-legume mixtures - VITA APRIANI; YULIANRI RIZKI YANZA; WULANSIH DWI ASTUTI; VINCENT NIDERKORN; RIMA S. H. MARTIN; JIDAN RAMADANI; WELAS SRI MULYATI; ANURAGA JAYANEGARA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Apriani V, Yanza YR, Astuti WD, Niderkorn V, Martin RSH, Ramadani J, Mulyati WS, Jayanegara A. 2025. Chemical composition, in vitro rumen profile and methane emission of fermented and non-fermented grass-legume mixtures. Biodiversitas 26: 869-878. This study aimed to evaluate the impact of several grass-legume mixtures, either fermented or non-fermented, on chemical composition, in vitro rumen fermentation profiles, and gas and methane production kinetics. Seven tropical leguminous plants were investigated, i.e., Indigofera zollingeriana, Calliandra calothyrsus, Clitoria ternatea, Centrosema pubescens, Leucaena leucocephala, Bauhinia purpurea, and Arachis pintoi. Each legume was combined with Pennisetum purpureum (elephant grass) in a 50:50 ratio, prepared in both fresh (non-fermented) and fermented (silage) forms. A completely randomized factorial design was employed, with legume type as the primary factor and fermentation status (non-fermented vs fermented) as the secondary factor (N = 5 replicates per treatment). Results revealed that legume type significantly influenced (P<0.05) In Vitro Dry Matter Digestibility (IVDMD) and In Vitro Organic Matter Digestibility (IVOMD), with I. zollingeriana demonstrating the highest digestibility values. A significant interaction between fermentation and legume type was observed in reducing methane gas production (P<0.05). Both legume inclusion and fermentation effectively lowered methane emissions (P<0.05), with the lowest levels recorded for C. calothyrsus and B. purpurea. The study concluded that incorporating tropical legumes, in both fermented and non-fermented forms, into elephant grass can improve digestibility and mitigate methane emissions, with Indigofera and Calliandra showing the most promising results, respectively.